Medical Student Education During COVID-19: Electronic Education Does Not Decrease Examination Scores. Issue 12 (December 2021) - Kronenfeld, Joshua P.; Ryon, Emily L.; Kronenfeld, Daniel S.; Hui, Vanessa W.; Rodgers, Steven E.; Thorson, Chad M.; Sands, Laurence R.
Background: During the COVID-19 emergency, medical students were mandated to remain home, creating challenges to providing education remotely for third-year clinical rotations. This study aims to assess student reception and investigate objective outcomes to determine if online learning is a suitable alternative. Methods: Medical students enrolled in the third-year surgical clerkship during COVID-19 were asked to participate in a survey. 19 of 27 (70%) students participated. Content, faculty-led lectures, and resident-led problem-based learning (PBL) sessions were assessed using a ten-point Likert scale. National Board of Medical Examiners (NBME) examination, weekly quiz, and oral examination scores were compared to previous years. Student t -tests compared the groups. Results: The median age was 25 years. Comparing in-person to electronic sessions, there was no difference in effectiveness of faculty sessions preparing students for NBME (6.2 vs. 6.7, P = .46) or oral examinations (6.4 vs. 6.8, P = .58); there was also no difference in resident-led PBL sessions preparing students for NBME (7.2 vs. 7.2, P = .92) or oral examinations (7.4 vs. 7.6, P = .74). Comparing this group to students from the previous academic year, there was no difference in weekly quiz (85.3 vs. 87.8, P = .13), oral examination (89.8 vs. 93.9, P = .07), or NBME examination (75.3 vs. 77.4, P = .33) scores. Discussion: Surgical medical didactic education can effectively be conducted remotely through faculty-led lectures and resident-led PBL sessions. Students did not have a preference between in-person and electronic content in preparation for examinations. As scores did not change, electronic education may be adequate for preparing students for examinations in times of crisis such as COVID-19.